中国加入WTO后重庆市国有企业存续对策分析 = Strategic analysis of state-owned enterprises in Chongqing city after China's accession to WTO - 田中强 Tian, Zhongqiang (2008)
In this paper, we examined the comparative advantages and challenges facing Chongqing’s SOEs and proposed various strategies to the government and SOEs in Chongqing area for their sustainable development. It is expected that the suggestions can prepare the government and SOEs for necessary adjustments and new challenges. (Dr. Leu Gwo-Jiun, Mike)